2017
DOI: 10.1080/2162402x.2016.1252895
|View full text |Cite
|
Sign up to set email alerts
|

An immunogenic WT1-derived peptide that induces T cell response in the context of HLA-A*02:01 and HLA-A*24:02 molecules

Abstract: The Wilms' tumor oncogene protein (WT1) is a highly validated tumor antigen for immunotherapy. WT1-targeted immunotherapy has been extensively explored in multiple human trials in various cancers. However, clinical investigations using WT1 epitopes have generally focused on two peptides, HLA-restricted to HLA-A*02:01 or HLA-A*24:02. The goal of this study was to identify new epitopes derived from WT1, to expand the potential use of WT1 as a target of immunotherapy. Using computer-based MHC-binding algorithms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Our study suggested that HSP70 and GPC3 are immunogenic eligible candidate proteins for peptide vaccination therapy, and peptides derived from these proteins can be administered and induce peptide-specific CTLs for patients with various GI cancers and the three common types of HLA alleles. It has been difficult to apply previous vaccination therapies to larger populations, considering that almost all peptides used previously are restricted to one HLA allele [4,5,31]. In contrast, our vaccination therapy used novel peptides which can bind to multi-HLA types including HLA-A*24:02, 02:01, and 02:06.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that HSP70 and GPC3 are immunogenic eligible candidate proteins for peptide vaccination therapy, and peptides derived from these proteins can be administered and induce peptide-specific CTLs for patients with various GI cancers and the three common types of HLA alleles. It has been difficult to apply previous vaccination therapies to larger populations, considering that almost all peptides used previously are restricted to one HLA allele [4,5,31]. In contrast, our vaccination therapy used novel peptides which can bind to multi-HLA types including HLA-A*24:02, 02:01, and 02:06.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, in idiopathic myelofibrosis (IM) [53], and in PMF [54][55][56] it emerged from the analyses that the WT1 gene is highly modulated. A T-cell receptor (TCR) that specifically reacts with WT1 peptide in the context of HLA-A * 24:02 has been identified [57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enrichment, we sought to apply automation to the peptide isolation and desalting step, and successfully incorporated additional on-cartridge modifications where reduction-alkylation, TMT tagging, and/or oxidation steps could be applied. A number of clinically relevant MHC-I displayed neoepitopes are known to contain cysteine and/or methionine residues (37,38), so chemical treatments that maximize the detection of such peptides are desired. We found, in contrast with work from others (19), that TMT tagging decreased the number of neoepitopes detected in our synthetic mixture, however this could be due to the much simpler or hydrophilic mixture with which we were working.…”
Section: Discussionmentioning
confidence: 99%